In situ Engineering of Hollow Porous Mo2C@C Nanoballs Derived From Giant Mo-Polydopamine Clusters as Highly Efficient Electrocatalysts for Hydrogen Evolution - Liu, Suli; Mu, Xueqin; Cheng, Ruilin; Lin, Shiyu; Zhu, Yang; Chen, Changyun; Mu, Shichun (Frontiers in Chemistry, 2020)
Low-cost and highly effective catalysts are crucial to the electrocatalytic hydrogen evolution reaction (HER). Among non-noble catalysts, molybdenum carbides are promising candidates because of their high reserves, stability, low cost, and structural diversity. In this work, we report a simple method to fabricate a hollow porous Mo2C@C nanoball through a hydrothermal preparation process of molybdenum precursors at high temperatures. Specifically, we have combined interfacial polymerization and the chelation effect to synthesize the Mo-polydopamine (Mo-PDA) precursor. As a result, Mo2C@C-3 only requires an ultralow Tafel slope (~55 mV dec−1) and low overpotential (η50 ≈ 167 mV) in a 0.5 M H2SO4 solution with long-term cycling stability. Besides, it also exhibits outstanding activity and stability under extensive HER testing in alkaline media. This study is promising for the development of advanced molybdenum carbide electrocatalysts toward electrochemical applications.